Standardised acoustic characterisation of sonic crystals noise barriers: Sound insulation and reflection properties. (15th December 2016) - Morandi, F.; Miniaci, M.; Marzani, A.; Barbaresi, L.; Garai, M.
Highlights: Sound insulation and sound reflection measurements on a sonic crystal are presented. Measurements are done according to EN 1793-2, EN 1793-5 and EN 1793-6. Strong and weak points of the measurement techniques are highlighted. The performances of sonic crystals and common noise barriers are compared. Abstract: This work presents sound insulation and sound reflection measurements conducted over sonic crystal noise barriers according to the European standards EN 1793-2, EN 1793-5 and EN 1793-6. In most of the reference literature, sound insulation and reflection properties of sonic crystals are measured or a diffuse sound field or in a direct sound field including the top and side edge diffraction effects together with the transmitted (or reflected) components. The aim of this work is to perform free-field measurements over a real-sized sample in order to window out all diffraction components and to verify the points of strength and weakness of the application of standardised measurements to sonic crystals. Diffuse field measurements in laboratory are also done for comparison purposes. Since the target frequency range for traffic noise spectrum is centred at around 1000 Hz, a finite element based parametric investigation is performed to design unit cells capable of generating band gaps in the one-third octave bands ranging from 800 Hz to 1250 Hz. Then, 3 × 3 m sonic crystal noise barriers are installed in the Laboratory of the University of Bologna and sound insulation and sound reflection measurements are performed according to the mentioned active standards for normal incidence. Sound insulation is measured for diffuse incidence too. The two methods give different results. The method more directly comparable to calculations is the free-field one. However, if on the one hand the application of a time window allows to compute the transmitted or reflected component only, on the other hand the time window itself limits the maximum width of the sample for which all reflections of the n -th order having a significant spectral content are included, and thus results critical in the analysis of this kind of noise barriers. Nevertheless, the standardised measurements allow a direct comparison between the performance of sonic crystals and common noise barriers.